Relation between chemical indices of soil and earthworm abundance under chemical fertilization - M. Iordache; I. Borza (Plant, Soil and Environment, 2010)
The study intended to establish how the dynamics of earthworms (Oligochaeta: Lumbricidae) changes in soil (abundance, biomass), under conditions of mineral fertilization with nitrogen and phosphorous in four different doses, in a 33-year experimental placement in the west of Romania, in wheat-soybean-maize-barley rotation. The soil indices taken into study were: pH, humus, total nitrogen, phosphorous and potassium. Statistical connections between the studied factors were realized using the dispersion analysis ANOVA and the SPSS Software (Statistical Package for the Social Sciences). The study showed an increase of earthworm abundance and biomass under conditions of chemical fertilization with nitrogen and phosphorous. The highest number of earthworms was recorded in the treatment with the largest dose of nitrogen fertilizer (by 85.85% higher compared to the control treatment). The greatest positive influence on earthworm abundance and biomass was manifested in humus and total nitrogen. The greatest negative influence on earthworm abundance was found in pH factor, while phosphorous content of soil exerted the greatest negative influence on earthworm biomass.